What is green infrastructure? A study of definitions in US city planning. Issue 3 (5th January 2022) - Grabowski, Zbigniew J; McPhearson, Timon; Matsler, A Marissa; Groffman, Peter; Pickett, Steward TA
Abstract : In response to interdependent challenges, city planners are increasingly adopting "green infrastructure" (GI). Reviewing 122 plans from 20 US cities, we identify what types of city plans address and define GI, including the concepts associated with GI, as well as the types, functions, and benefits of GI. The most common plans that feature GI, some of which focus exclusively on GI, comply with US Clean Water Act regulations for stormwater and sewer systems. Municipalities also address GI through diverse planning processes, including the creation of comprehensive citywide plans. Many of these plans (~40%) do not explicitly define GI. When they do, stormwater concepts predominate, followed by landscape concepts, along with an emergent emphasis on integrating GI with other built infrastructure systems. Large differences in GI types, functions, and benefits across concepts, plan types, and cities indicate a need for synthesis of GI definitions. To facilitate this synthesis, we provide a database of GI definitions from plans used in our analysis. We conclude with a broad synthetic definition of GI to provide clarity and stimulate discussion in rapidly evolving planning, policy, and research arenas.